Исследование динамики ротора газоперекачивающего агрегата при нарушениях посадки вала в подшипниках скольжения - Сапрыкин, С. А.; Дутчак, А. И. (НТУ "ХПИ", 2006)
Здійснено теоретичне дослідження динаміки ротора газотурбінних двигунів при порушенні посадки валу в підшипниках ковзання. Встановлено, що по причині такого порушення відбувається поступов зменшення відносного ексцентриситету розміщення валу у підшипнику, що сприяє виникненню стійких автоколивань ротора на масляній плівці, і тим самим є збудником інтенсивних вібрацій підшипників ротора.

The theoretical research of dynamics (changes) of a rotor gas of turbine of engines is executed at infringements of landing (planting) of the shaft in bearings of sliding. Is established, that in a consequence of such infringement there is a gradual reduction relative center of accommodation of the shaft in the bearing, that accompanies occurrence of proof auto fluctuations of a rotor on an oil film, and by that is the activator of intensive vibrations of bearings of a rotor.
Keywords: ГПА; газотурбинный двигатель; ГТД; дифференциальные уравнения; автоколебания; область устойчивости